(untitled) (Global Journal of Medical Research, 2022)
Sepsis is a condition that occurs when the body produces an unbalanced immune response to an infection Septic shock is the most serious manifestation of this infection which increases with aggravation of maternal and perinatal morbidity and mortality Within the pharmacological therapeutic options the cornerstone of this entity is broad-spectrum antibiotic therapy however there are other drugs that can be used as adjuvants in the context of sepsis and among them are immunoglobulins Currently there is little scientific evidence about the use of immunoglobulins in pregnant patients and in Colombia there is only one case report published so far The objective of this patient report is to present the case of a primipregnant woman with a pregnancy of 16 3 weeks diagnosed with septic shock who was administered immunoglobulin G enriched with IgM IgA which had an excellent response to the established treatment and satisfactory evolution without presenting maternal or fetal adverse effects to the drug